Effectiveness of Zingiber montanum Herbal Compress Remedy for Pain Management: An Updated Systematic Review and Meta-Analysis - Kanjana Worasing; Bunleu Sungthong; Wiraphol Phimarn (MDPI AG, 2023)
The Zingiber montanum herbal compress remedy is a type of herbal medicine that can be used as an alternative treatment for improving pain symptoms. This study aimed to evaluate the clinical efficacy of a Z. montanum herbal compress remedy for pain relief. PubMed, Scopus, ScienceDirect, and Thai databases were systematically searched for relevant articles published from inception to December 2022. Only randomized clinical trials (RCTs) wherein the efficacy of the Z. montanum remedy was compared to that of a placebo or non-steroidal anti-inflammatory drugs (NSAIDs) were included. Six RCTs with a total of 812 patients were included in the analysis. The efficacy of the Z. montanum remedy had a significantly decreased pain score compared to the placebo (SMD = −0.63; 95% CI = −1.20, −0.06; I2 = 90%), but there was no significant difference when compared to NSAIDs (SMD = −0.61; 95% CI = −1.41, 0.81; I2 = 73%). Moreover, the efficacy of the Z. montanum remedy in terms of the flexibility score (SMD = 0.59; 95% CI −0.56, 1.74; I2 = 86.0%) and quality of life (SMD = 0.34; 95% CI −0.38, 1.05; I2 = 81.0%) was similar to that of the placebo. This meta-analysis demonstrates that the use of the Z. montanum herbal compress remedy significantly reduces the pain scores reported by patients.